How significant are supplier selection criteria to the performance of a company? Reviewing Kuantan, Pahang Textile Industry - Haziman, Zakaria; Diyana, Kamarudin; Faiz, Azizul; Mazila, Mat Yuden; Ame, Abdullah (GBMR, 2023)
Purpose: The selection of a company's suppliers is crucial because they are one of the most influential factors that determine the success or failure of the company. Every business wants a reasonable price, acceptable quality and prompt delivery. Poor supplier selection can lead to performance problems that will affect the company. In particular, the company will lose customers and revenue. Design/methodology/approach: A quantitative research methodology was used to assess the objectives of the study, which relate to the textile industry in Kuantan, Pahang. The analysis of the study includes descriptive analysis, reliability analysis (Cronbach's alpha > 0.70), normality analysis (histogram), correlation analysis (person correlation) and multiple regression analysis. Result: The results show that the quality variables are rejected, while the price and cost variables and delivery are accepted in relation to business performance. Research limitations/implications: There There are various methods for evaluating a reliable supplier, including "decision theory techniques", which are recommended in the literature to assist companies' decision-making. In this study, decision theory is used to evaluate suppliers based on criteria and the profit that the company can gain from choosing the supplier. Practical implications: The relationship between supplier selection factors and company performance has been sufficiently demonstrated by considering the study result. From this, a suggestion can be made for future improvements in the research, such as changes in the business environment or location. This may help researchers to improve the validity of their work. Originality/value: This problem results from the expensive and inferior purchase of raw materials by the supplier. The aim of this study is, therefore, to assist companies in selecting a reliable supplier. The profitability and competitiveness of a company also depend on the selection of reliable suppliers.